Caste, Ethnicity and Poverty in Rural India - Ira N. Gang; Kunal Sen; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2002)
This paper analyzes the determinants of rural poverty in India, contrasting the situation of the Scheduled Caste (SC) and Schedule Tribe (ST) households with the non-scheduled population. The incidence of poverty among SC and ST households is significantly higher than non-scheduled households. Using a probit decomposition analysis, we decompose the difference in the poverty rates between the scheduled castes (or tribes) and non-scheduled households into a part explained by the differences in characteristics and a part explained by the differences in probit coefficients. The paper finds that for SC households, differences in characteristics explain the gap in poverty rates more than differences in coefficients; while for ST households, it is the reverse. Differences in educational attainment explain about one quarter of the poverty gap for both social groups. Occupational structure strongly matters in determining the poverty gap for both SC and ST, as does differences in returns to individual occupations. While poverty rates are not very different between SC and ST households, the analysis suggests that the underlying factors for the higher incidence of poverty in these social groups are to a large extent different.
Keywords: J15; O12; I32; 330; poverty; caste; ethnicity; probit decomposition; Ländliche Armut; Armut; Soziale Schicht; Ethnische Gruppe; Schätzung; Indien